Does Governance Matter for Outward FDI? Evidence from the European Union Member States - Bogusława Dobrowolska; Tomasz Dorożyński; Anetta Kuna‑Marszałek (Comparative Economic Research)
Our principal aim is to assess the role of governance companies’ active internationalisation. We first measured and compared the degree of institutional quality among the 28 European Union Member States (EU–28) between 2004 and 2021 using the authorship synthetic index of governance quality (SIGQ) values. In the second step, we assessed outward foreign direct investment (OFDI) projects measured by their relative value to the GDP per capita in each member state. Finally, we correlated the overall quality of governance (GQ) and its six dimensions with OFDI in the EU–28 (including the UK). We employed numerous statistical tools, i.e., hierarchical cluster analysis, contingency analysis, synthetic index values, and descriptive statistics. We used the Worldwide Governance Index (WGI) to assess the GQ in the EU–28 for 2004–2021. The statistical analysis results revealed a positive relationship between the quality of governance and the OFDI. The most important of the partial variables was the rule of law, which reflects perceptions of the degree to which individuals and actors trust and adhere to social rules. Our research demonstrates that policymakers should consider the importance of institutional quality indicators in supporting domestic companies “to go abroad”. The primary input delivered by the study to the current body of knowledge about OFDI involves identifying the relationship between GQ in all the EU–28 (“old” and “new”) using the SIGQ index.